COLLABORATIVE CARE: EXPLORING THE DYNAMICS BETWEEN NURSES, SOCIAL WORKERS, AND PSYCHOLOGISTS IN HEALTHCARE ENVIRONMENTS - Maryam Jurayyd Alruwaili, Faten Fahad Mohammed Alharbi, Jamal Abdulaziz Kordy Aldhafeeri, Nashmiah Hamoud Graad Alharby, Fatin Abbar Matleq Aldhafeeri, Eman Shati Funaysan Aldhafeeri, Fatimah Furaih Sh Aldhafeeri, Hanan Shati Funaysan Aldhafeeri, (Chelonian Research Foundation, 2022)
Collaborative care among healthcare professionals is essential for providing comprehensive and effective patient care. This study explores the dynamics between nurses, social workers, and psychologists in healthcare environments, focusing on their roles, interactions, and impact on patient outcomes and job satisfaction. A mixed-methods approach was employed, involving surveys and semi-structured interviews with healthcare professionals from various settings. The findings reveal that effective interprofessional collaboration is associated with improved patient outcomes, increased job satisfaction, and reduced burnout among healthcare professionals. Key factors contributing to successful collaboration include clear communication, mutual respect, shared decision-making, and supportive organizational culture. Barriers to collaboration, such as power imbalances, role ambiguity, and limited resources, are also discussed. The study highlights the need for targeted interventions and policies to foster collaborative care and optimize the contributions of nurses, social workers, and psychologists in healthcare environments. Keywords: collaborative care, interprofessional collaboration, nurses, social workers, psychologists, healthcare environments, patient outcomes, job satisfaction